1976
DOI: 10.1111/j.1751-1097.1976.tb06770.x
|View full text |Cite
|
Sign up to set email alerts
|

Action Spectra for Photoaccumulation of Green and Colorless Euglena: Evidence for Identification of Receptor Pigments

Abstract: Phototaxis action spectra have been determined in three different types of Euglena gracilis; green and dark-bleached cells containing the stigma and streptomycin-treated white mutant with an absorptionless stigma. In all three types of microorganisms the flavin containing paraflagellar body is present. The shape of the action spectrum is the same for the three types of cells and proportional to the absorption spectrum of flavoproteins. It has been shown that the structure of the action spectrum does not depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

1976
1976
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(49 citation statements)
references
References 21 publications
1
46
0
2
Order By: Relevance
“…Os testes foram realizados com algas Euglena gracilis em meio mineral e orgânico preparado conforme descrição feita por Checcuci et al (1976) As culturas preparadas nas condições descritas anteriormente foram mantidas em uma única cultura de 300 mL, tratadas durante um período de uma semana a fim de se manter homogeneidade do meio para a aplicação dos testes futuros. Esta cultura foi subdivida em 6 frações de 50 mL, as quais receberam posteriormente a adição da solução das amostras de água de abastecimento e efluentes (amostras testes).…”
Section: Materiais E Métodosunclassified
“…Os testes foram realizados com algas Euglena gracilis em meio mineral e orgânico preparado conforme descrição feita por Checcuci et al (1976) As culturas preparadas nas condições descritas anteriormente foram mantidas em uma única cultura de 300 mL, tratadas durante um período de uma semana a fim de se manter homogeneidade do meio para a aplicação dos testes futuros. Esta cultura foi subdivida em 6 frações de 50 mL, as quais receberam posteriormente a adição da solução das amostras de água de abastecimento e efluentes (amostras testes).…”
Section: Materiais E Métodosunclassified
“…This view is supported by more recent work of Benedetti and Checcucci [l] in which the paraflagellar body of Euglena, long thought to be the photoreceptor organelle, was found to exhibit flavin-like fluorescence. Moreover, even bleached strains of Euglena have flavin-type action spectra for photoaccumulation [3]. Mikolajczyk and Diehn, however, have shown that only the step-down (inverse) photophobic response of Euglena is mediated by a flavin pigment, while the step-up (direct) response most likely involves a different receptor pigment [20].…”
Section: Photomovement Of Microorganismsmentioning
confidence: 99%
“…The fluence rate of light incident upon the paraflagellar swelling may change during the course of cell rotation due to the screening organelle, stigma (2,8,22). On the other hand, somewhat different models, based on the orientation of pigment, were proposed (6,9,10).…”
Section: Resultsmentioning
confidence: 99%